KONFLIK BATIN TOKOH DALAM NOVEL RAHASIA BATIK BERDARAH - Ortensia, Soraya; Priyadi, Antonius Totok; Seli, Sesillia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the results of the analysis of the inner conflicts of the characters in the novel Secrets of Rahasia Batik by Leikha Ha. This approach uses descriptive methods, qualitative research forms, and literary psychology approaches. The data source of this research is the novel Secret of Rahasia Batik by Leikha Ha with data in the form of inner conflict research in the form of words, phrases and sentences that lead to the object of analysis. Data collection techniques using documentary study techniques. The technique of testing the validity of the data was carried out with persistence of observation, triagulation, and referential competence. The results of this study indicate that the main character's inner conflict includes fear, depression, disappointment, hurt, anxiety and additional characters which include forms of inner conflict, namely guilt, anxiety, sadness, hatred, fear, disappointment, jealousy, dislike. and angry. The lesson plans for Indonesian language subjects have been successfully designed in accordance with competencies 3.9 and 4.9 by utilizing the novel "Rahasia Batik" as learning material.